1996
DOI: 10.1152/ajpregu.1996.270.4.r864
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of weight cycling in obese spontaneously hypertensive rats

Abstract: We mimicked human weight cycling in the obese spontaneously hypertensive rat (SHROB) model of genetic obesity. A 12-day very low calorie diet (VLCD; 16.7% of baseline calories) was alternated with 4-6 wk of ad libitum chow refeeding for three cycles. Control SHROB ate chow ad libitum. VLCD induced rapid weight loss, but during refeeding all the lost weight was regained. Final body weight was higher in cycled rats than in ad libitum controls (149 +/- 5 vs. 117 +/- 7% of initial baseline). Less weight was lost a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 23 publications
1
46
0
Order By: Relevance
“…Therefore, some patients choose to starve occasionally rather than follow an energy-deficient diet regularlyFa fact that maintains the weight loss-regain cycle. Recurrent weight losses and weight cycling have been proposed to exacerbate obesity by increasing metabolic efficiency both in animals 29 and in humans. 13 A small experiment on five normal-weight female subjects showed that two consecutive weight cycles of 4 kg lead to significant decreases in lean body mass, serum tri-iodothyronine and thyroxine concentrations, and in resting energy expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, some patients choose to starve occasionally rather than follow an energy-deficient diet regularlyFa fact that maintains the weight loss-regain cycle. Recurrent weight losses and weight cycling have been proposed to exacerbate obesity by increasing metabolic efficiency both in animals 29 and in humans. 13 A small experiment on five normal-weight female subjects showed that two consecutive weight cycles of 4 kg lead to significant decreases in lean body mass, serum tri-iodothyronine and thyroxine concentrations, and in resting energy expenditure.…”
Section: Discussionmentioning
confidence: 99%
“…13 Similar to our findings for non-obese individuals, in a population of non-obese workers, Itoh et al 16 found no association between weight cycling and hypertension. Potential biological mechanisms by which weight cycling might be linked to hypertension shown in animal studies include abdominal fat accumulation and sympathetic activity, 27 as well as stress caused by rapid fluctuations in weight. 28 We used a strict definition of weight cycling, applying the information we had on intentionality of short-term weight change, since intentionality of weight change has been shown to be associated with health behaviour 29 and disease risk.…”
Section: Short-term Weight Change and Hypertension M Schulz Et Almentioning
confidence: 99%
“…[1][2][3] There have been several animal studies that have shown that hypertension can be caused or exacerbated by cycles of fasting and refeeding. [4][5][6][7] Initially, during the fast, there is a reduction in blood pressure. This reduction was shown, in one study, to be related to the nutritional state as opposed to the actual weight.…”
Section: Introductionmentioning
confidence: 99%